2014
DOI: 10.1515/ijsl-2014-0004
|View full text |Cite
|
Sign up to set email alerts
|

Informal signs as expressions of multilingualism in Chisinau: how individuals shape the public space of a post-Soviet capital

Abstract: Informal and transient displays of written language such as graffiti, announcements and notes attached to walls and lampposts form an integral part of an urban linguistic landscape. Especially within multilingual contexts, individuals constantly shape the public space by the languages they use and make language choices that do not always reflect official language policies, commonly held perceptions or the demographic makeup within a certain area. The capital of the Republic of Moldova, Chisinau, proves to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
1
1
0
1
Order By: Relevance
“…Another limitation concerns methodological representativity (as discussed above). Our results show a very strong domination of Swedish language messages (only 3% were in another language than Swedish, which can be compared to another study in Moldavia by Muth [ 23 ] which showed how public spaces preserved Russian language expressions despite the national policy stating that Romanian Moldovan is the official language). However, this is certainly not true for bulletin boards all across Sweden.…”
Section: Discussionsupporting
confidence: 62%
“…Another limitation concerns methodological representativity (as discussed above). Our results show a very strong domination of Swedish language messages (only 3% were in another language than Swedish, which can be compared to another study in Moldavia by Muth [ 23 ] which showed how public spaces preserved Russian language expressions despite the national policy stating that Romanian Moldovan is the official language). However, this is certainly not true for bulletin boards all across Sweden.…”
Section: Discussionsupporting
confidence: 62%
“…The Russian language is widely used for interethnic communication and is strongly influenced by the position of Transnistria, where it remains the primary language. Nearly half of Moldova's remaining population also know Russian to some extent and use the language in a much wider range of contexts than officials usually report (Muth 2014). However, the proportion of active Russian speakers, who use the language in everyday life, in Moldova excluding Transnistria is 14% (Aref'ev 2015: 33).…”
Section: Post-soviet Russianmentioning
confidence: 99%
“…Фотографии затем помещают в корпус (базу данных), где каждый снимок/надпись имеет свой код, включающий место и время, когда была сфотографирована надпись, языки, материал (анализ материала позволяет отличить временные надписи от постоянных) и тип надписи (официальный, коммерческий, неформальный). Для обеспечения открытости и прозрачности (transparency) информации некоторые исследователи открывают доступ к своим корпусам он-лайн (Muth 2014с).…”
Section: языковые ландшафтыunclassified